Social Responsibility of Business as a Potential of Russian-African Relations (Empirical Research Experience in the Countries of the African Continent) - KHARITONOVA Elena Vladimirovna (Ученые записки Института Африки Российской академии наук)
The image of Russia and the credibility of its policies are closely linked to the image of its business. The positive or negative perception of Russia as a whole largely depends on how Russian companies do business in Africa. The article presents a study of the social perceptions of Africans of the social responsibility of businesses operating in African countries. A comparative analysis of the representations of the «African side» and the «Russian side» is demonstrated. The empirical basis of the study was the data collected by the author. The results obtained demonstrate significant differences in the perceptions of social responsibility of business among African and Russian respondents. In some cases, diametrically opposite results were obtained. The data indicate that there is a problem area at the level of social perceptions – a potential basis for a lack of understanding or even a conflict between the Russian and the African sides. The author concludes that the ideas of the «correct» models of social responsibility of business among Africans are connected with their value system, with the understanding of «social justice». Knowledge of preferred and rejected business social responsibility models among African partners can be a competitive advantage in establishing Russian-African business relations. It can be assumed that information about the «problem areas» will help to avoid communication errors and «traps» associated with ignorance, misunderstanding and disregard of the social perceptions of African partners. The author suggests that knowledge of the social perceptions, needs, moods, «requests» of the African side is an important condition for building effective business communications and can contribute to the realization of the potential of the Russian- African partnership.